Circadian influences on myocardial infarction - Virag, Jitka A. I.; Lust, Robert M. (Frontiers in Physiology, 2014)
Components of circadian rhythm maintenance, or “clock genes”, are found in all peripheral tissues, including the heart, and influence such diverse phenomena as cytokine expression immune cells, metabolic activity of cardiac myocytes, and vasodilator regulation by vascular endothelial cells. Whether circadian patterns are causally related to the observed periodicity of events, or whether they are simply epi-phenomena is not well established, but a few studies suggest that the circadian effects likely are real in their impact on cardiovascular disease incidence. Cycle disturbances may be harbingers of predisposition and subsequent response to acute and chronic cardiac injury, and identifying the complex interactions of circadian rhythms and cardiovascular disease may provide insights into possible preventative and therapeutic strategies for susceptible populations.